Interprofessional work in operating rooms: a qualitative study from Sri Lanka - Illesinghe, V.J.; Guruge, S.; Gamage, B.; Espin, S. (BMC Surgery, 2016)
Attached

Background: A growing body of research shows links between poor teamwork and preventable surgical errors. Similar work has received little attention in the Global South, and in South Asia, in particular. This paper describes surgeons’ perception of teamwork, team members’ roles, and the team processes in a teaching hospital in Sri Lanka to highlight the nature of interprofessional teamwork and the factors that influence teamwork in this setting. Methods: Data gathered from interviews with 15 surgeons were analyzed using a conceptual framework for interprofessional teamwork. Results: Interprofessional teamwork was characterized by low levels of interdependency and integration of work. The demarcation of roles and responsibilities for surgeons, nurses, and anesthetists appeared to be a strong element of interprofessional teamwork in this setting. Various relational factors, such as, professional power, hierarchy, and socialization, as well as contextual factors, such as, patriarchy and gender norms influenced interprofessional collaboration, and created barriers to communication between surgeons and nurses. Junior surgeons derived their understanding of appropriate practices mainly from observing senior surgeons, and there was a lack of formal training opportunities and motivation to develop non-technical skills that could improve interprofessional teamwork in operating rooms. Conclusions: A more nuanced view of interprofessional teamwork can highlight the different elements of such work suited for each specific setting. Understanding the relational and contextual factors related to and influencing interprofessional socialization and status hierarchies can help improve quality of teamwork, and the training and mentoring of junior members
Keywords: Interprofessional work; Sri Lanka; Surgical errors; Teamwork